Der Architekt in der Frühen Neuzeit Ausbildung - Karrierewege - Berufsfelder - Bognár, Anna-Victoria (Höfische Kultur Interdisziplinär (HKI) - Schriften und Materialien des Rudolstädter Arbeitskreiss zur Residenzkultur, 2020)
The profession of architect underwent the decisive stages of its professionalisation during the early modern period of the Holy Roman Empire (approx. 1500-1800). As a rule, multiple training courses in the artistic, military and scientific fields prepared the architects for a broad range of professional tasks. As "Baumeister" (head architects) with building authorities, they introduced an efficient division of labour in design, planning, execution and administration, and were sometimes able to pursue remarkable careers. This volume examines the cultural, social and administrative factors that contributed to the artistic work of architects.